PENDIDIKAN KARAKTER MENURUT IBNU SINA DAN RELEVANSINYA DENGAN PEMBANGUNAN KARAKTER DI INDONESIA - Nur Indah Sari (AS-SALAM, 2014)
Analysing education in Indonesia is still not focused on the ideal educational purposes , this happens because of the moral crisis that occurs in almost all lines and moral crisis that occurred among students , so that character education is becoming increasingly urgent . Ibn Sina is one of the leading thinkers very intense and critical in improving education and encouraging orientation toward character education . Character education here is education in accordance with the expectations of society, which in addition has also qualified personal knowledge, morality, and morality in public life growing global current and future. The purpose of this study is the study aimed to determine by Ibn Sina Character Education and Its Relevance to Character Development in Indonesia . From the analysis it can be seen that according to Ibn Sina's character education is very relevant at all to the character development in Indonesia. Because the concept of education offered by Ibn Sina ranging from educational goals, curriculum, teaching methods, teacher education and the implementation of the law is in accordance with the demands of the current era.